2023
DOI: 10.1007/s40618-023-02115-2
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating miR-26b-5p and miR-451a as diagnostic biomarkers in medullary thyroid carcinoma patients

Abstract: Purpose/methods The determination of tumour biomarkers is paramount to advancing personalized medicine, more so in rare tumours like medullary thyroid carcinoma (MTC), whose diagnosis is still challenging. The aim of this study was to identify non-invasive circulating biomarkers in MTC. To achieve this goal, paired MTC tissue and plasma extracellular vesicle samples were collected from multiple centres and microRNA (miRNA) expression levels were evaluated. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The diagnostic performance of the two miRNAs was validated in a second independent cohort of MTC patients and control subjects using digital PCR. ROC curve analyses confirmed the high diagnostic role of miR-26b-5p and miR-451a [49].…”
Section: Circulating Mirnas In Mtcmentioning
confidence: 58%
See 1 more Smart Citation
“…The diagnostic performance of the two miRNAs was validated in a second independent cohort of MTC patients and control subjects using digital PCR. ROC curve analyses confirmed the high diagnostic role of miR-26b-5p and miR-451a [49].…”
Section: Circulating Mirnas In Mtcmentioning
confidence: 58%
“…However, in this case, specificity and sensitivity were too low to propose this miRNA as a new circulating biomarker for MTC. Worth noting, only one study has been performed to date on plasma extracellular vesicles (pEVs) [49], which reported an upregulation in miR-26b-5p and miR-451a in MTC patients with significant diagnostic performance. These miRNAs had not been previously identified, probably due to the different biological samples used in other studies.…”
Section: Circulating Mirnas In Mtcmentioning
confidence: 99%
“…miR-451a is known to be involved in various cancers, including medullary thyroid carcinoma 29 , bladder cancer 30 , pancreatic cancer 31 , colorectal cancer 32 , and in ammatory diseases 33 . In a study conducted by Abdul et al, the relative expression levels of miRNAs in tumorous and normal adjacent tissues of Triple-negative breast cancer (TNBC) patients were determined using qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-451a and miR-26b-5p as potential markers for MTC expression levels were high in MTC patients, and their expression showed a decline in cancer-free patients during follow-up. The findings offer a promising approach for MTC diagnosis using miR-26b-5p and miR-451a, potentially leading to the development of more efficacious strategies for treating patients with MTC [ 38 ].…”
Section: Deregulation Of Mirnas In Thyroid Cancer and Mtcmentioning
confidence: 99%